THE MEANING OF THE COLOR COMPOSITION IN THE VISUAL ARTS - Abatov Jalgasbay Orınbaevich; Ismailov Alisher Muratbaevich; Turabaev Mansur Alimovich (Journals Park Publishing, 2022)
In this article we wrote about how to enrich a composition with flowers, how to use colors and how to convey them to people, about the influence of colors on human psychology, character and health. The color of the human environment has a direct impact on human psychology, we briefly explained the possibility of controlling human psychology through color scales.
Keywords: color; composition; static